Conservation status of Brachycephalus toadlets (Anura: Brachycephalidae) from the Brazilian Atlantic rainforest - Bornschein, Marcos R. [UNESP]; Pie, Marcio R.; Teixeira, Larissa [UNESP] (MDPI, 2019)
The number of described anurans has increased continuously, with many newly described species determined to be at risk. Most of these new species inhabit hotspots and are under threat of habitat loss, such as Brachycephalus, a genus of small toadlets that inhabits the litter of the Brazilian Atlantic Rainforest. Of 36 known species, 22 were described in the last decade, but only 11 have been assessed according to the IUCN Red List categories, with just one currently listed as Critically Endangered. All available data on occurrence, distribution, density, and threats to Brachycephalus were reviewed. The species extent of occurrence was estimated using the Minimum Convex Polygon method for species with three or more records and by delimiting continuous areas within the altitudinal range of species with up to two records. These data were integrated to assess the conservation status according to the IUCN criteria. Six species have been evaluated as Critically Endangered, five as Endangered, 10 as Vulnerable, five as Least Concern, and 10 as Data Deficient. Deforestation was the most common threat to imperiled Brachycephalus species. The official recognition of these categories might be more readily adopted if the microendemic nature of their geographical distribution is taken into account.
Keywords: Conservation; Critically endangered; Data deficient; Deforestation; Fire; Invasion of exotic plants; Protected areas; Public policy; Timber harvest